2007
DOI: 10.1097/pec.0b013e3181568039
|View full text |Cite
|
Sign up to set email alerts
|

Frena Tears and Abusive Head Injury

Abstract: Tears of the lingual and labial frena have been associated with accidental and nonaccidental injury. Three cases of infants are presented who were evaluated in the hospital with frena tears which were not recognized as manifestations of abuse, discharged home, and subsequently returned with manifestations of severe abusive head injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 3 publications
1
47
0
1
Order By: Relevance
“…54,55 The majority of sentinel injuries are bruises, intraoral injuries, including frena tears, or fractures. [57][58][59][60] Physicians sometimes underappreciate the significance of sentinel injuries or attribute them to noninflicted trauma, self-inflicted trauma, or medical disease. 54 Physicians may overlook injuries that are commonly considered accidental in ambulatory children but have higher specificity for abuse in young infants.…”
Section: Missed Opportunities For Diagnosing Physical Abusementioning
confidence: 99%
“…54,55 The majority of sentinel injuries are bruises, intraoral injuries, including frena tears, or fractures. [57][58][59][60] Physicians sometimes underappreciate the significance of sentinel injuries or attribute them to noninflicted trauma, self-inflicted trauma, or medical disease. 54 Physicians may overlook injuries that are commonly considered accidental in ambulatory children but have higher specificity for abuse in young infants.…”
Section: Missed Opportunities For Diagnosing Physical Abusementioning
confidence: 99%
“…Over the past 25 years, research has repeatedly highlighted missed opportunities to evaluate and diagnose abuse in young, injured children, resulting in children suffering from undiagnosed injuries as well as ongoing abuse. [36][37][38][39][40][41][42][43] Research has also revealed that racial and socioeconomic status (SES)-based biases influence decision-making regarding child abuse evaluations and diagnoses. 17,31,35,44,45 A single institution study of unwitnessed TBI in infants showed that implementation of a guideline for universal occult fracture evaluation in this population can eliminate racial and SES-based disparities and might increase the detection of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Several such sentinel injuries have been suggested on the basis of case reports and retrospective analyses of cohorts of abused children. [22][23][24] However, these studies have not been able to estimate the likelihood of abuse in children with these injuries because they have not identified the denominator of children presenting with these injuries. One large analysis of the association between fractures and abuse was able to overcome this challenge, but was limited to children who were admitted to the hospital.…”
mentioning
confidence: 99%